Deletion of the Alzheimer’s disease risk gene Abi3 locus results in obesity and systemic metabolic disruption in mice - Smith, Daniel C.; Karahan, Hande; Wijeratne, H. R. Sagara; Al-Amin, Mamun; McCord, Brianne; Moon, Younghye; Kim, Jungsu (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) genetics studies have identified a coding variant within ABI3 gene that increases the risk of developing AD. Recently, we demonstrated that deletion of the Abi3 gene locus dramatically exacerbates AD neuropathology in a transgenic mouse model of amyloidosis. In the course of this AD project, we unexpectedly found that deletion of the Abi3 gene locus resulted in a dramatic obese phenotype in non-transgenic mice. Here, we report our investigation into this serendipitous metabolic finding. Specifically, we demonstrate that mice with deletion of the Abi3 gene locus (Abi3–/–) have dramatically increased body weight and body fat. Further, we determined that Abi3–/– mice have impaired energy expenditure. Additionally, we found that deletion of the Abi3 gene locus altered gene expression within the hypothalamus, particularly within immune-related pathways. Subsequent immunohistological analysis of the central nervous system (CNS) revealed that microglia number and area were decreased specifically within the mediobasal hypothalamus of Abi3–/– mice. Altogether, this investigation establishes the functional importance of the Abi3 gene locus in the regulation of systemic metabolism and maintenance of healthy body weight. While our previous findings indicated the importance of Abi3 in neurodegeneration, this study indicates that Abi3 related functions are also essential for metabolic regulation.